One of the Esteemed Commander; Yakup Şevki Pasha - Taşkın, Ü. (Fırat University, 2015)
Yakup Şevki Pasha was born in the Kharpoot. He was a soldier who have provided important services in the years of First World War and The Turkish War of Independence for army. He has all the features of a soldier and was rewarded because of successes that he has acquired during his tenure. He has courageous, cool, stubborn, hopeful and was renowned as a fair commander. He was a beloved person by retinue due to these properties. In this paper it will be examined, Yakup Şevki Pasha’s personality, biography, activities

Harputlu olan Yakup Şevki Paşa, I. Dünya Savaşı ve Kurtuluş Savaşı yıllarında önemli hizmetler vermiş bir askerdi. Bir askerde bulunması gereken bütün özelliklere sahipti ve görevdeyken elde ettiği başarılarından dolayı taltif edildi. Cesaretli, soğukkanlı, inatçı, umudunu kaybetmeyen, adil bir komutan olarak bilinirdi. Bu özelliklerinden dolayı maiyeti tarafından sevilen bir kişiydi. Bu çalışmada Yakup Şevki Paşa’nın faaliyetleri, şahsiyeti ve biyografisi incelenecektir
Değerli Kumandanlarımızdan Yakup Şevki Paşa